Dosimetry-based treatment planning for molecular radiotherapy: a summary of the 2017 report from the Internal Dosimetry Task Force - Stokke, Caroline; Gabiña, Pablo Minguez; Solný, Pavel; Cicone, Francesco; Sandström, Mattias; Gleisner, Katarina Sjögreen; Chiesa, Carlo; Spezi, Emiliano; Paphiti, Maria; Konijnenberg, Mark; Aldridge, Matt; Tipping, Jill; et al. (EJNMMI physics, 2017)
BACKGROUND: The European directive on basic safety standards (Council directive 2013/59 Euratom) mandates dosimetry-based treatment planning for radiopharmaceutical therapies. The directive comes into operation February 2018, and the aim of a report produced by the Internal Dosimetry Task Force of the European Association of Nuclear Medicine is to address this aspect of the directive. A summary of the report is presented. RESULTS: A brief review of five of the most common therapy procedures is included in the current text, focused on the potential to perform patient-specific dosimetry. In the full report, 11 different therapeutic procedures are included, allowing additional considerations of effectiveness, references to specific literature on quantitative imaging and dosimetry, and existing evidence for absorbed dose-effect correlations for each treatment. Individualized treatment planning with tracer diagnostics and verification of the absorbed doses delivered following therapy is found to be scientifically feasible for almost all procedures investigated, using quantitative imaging and/or external monitoring. Translation of this directive into clinical practice will have significant implications for resource requirements. CONCLUSIONS: Molecular radiotherapy is undergoing a significant expansion, and the groundwork for dosimetry-based treatment planning is already in place. The mandated individualization is likely to improve the effectiveness of the treatments, although must be adequately resourced.
Keywords: Dosimetry; Molecular radiotherapy; Treatment planning